KKN PPM berbasis sumber daya pesisir pada wanita nelayan di Kabupaten Barru - Ernawati S. Kaseng; Taty Sulastry; Abd. Rahman (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The program activities of the KKN PPM aims toenhance students' awareness and empathy towards theproblems facing the village community service learning, sothat changes the behavior of the students, and the target group.In addition to empowering the women of fishermen VillagesPancana and Alumpangeng Sub Tanete Rilau, Barru Regencyin the framework of the achievement of the targets have beenformulated. Specific targets to be achieved is the increase inproduction and quality of processing fish that used to offer itonly drained, but through KKN PPM is, people are invited tofish processing into other products such as meatballs andshredded fish, brain-brain-based foods as well as other fish.With a better processing and hygienic and attractive packaging,strengthening the institutional system a group of marine fish,the fisherman's increased income and crafters community dueto the production of processed fish products increased, the fishof the sea be qualified and have high competitiveness. As wellas the formation of the villages of Pancana and Alumpangengas a model village for the production of sea fish products thatare valued economically. The strategy used is theempowerment of the target group approach to PRE(Partisipatory Rural Appraisal) method, with the education,training, mentoring, demplot and equipped with the techniqueslearned while working (learning by doing). Plan activitiesinclude: demplot, training and mentoring are first carried outsocialization through counseling. Training materials include:(1) Production technology and application of naturalpreservative sea fish, (2) technology of the manufacture ofprocessed sea fish food (the brain-the brain, Nuggets,meatballs and shredded fish), (3) hygienic food manufacturingtechnology and packaging that menarikdengan energy/firewood, (4) Labelisasi PIRT marine fish food products thatare attractive and hygienic, (5) the application of the healthykitchen practices, (6) sea fish food manufacturing technologyand improved nutrition, (7) institutional strengthening of thegroup, (8) the strengthening of network marketing.